2020
DOI: 10.1261/rna.076687.120
|View full text |Cite
|
Sign up to set email alerts
|

Viral subversion of nonsense-mediated mRNA decay

Abstract: Viruses have evolved in tandem with the organisms that they infect. Afflictions of the plant and animal kingdoms with viral infections have forced the host organism to evolve new or exploit existing systems to develop the countermeasures needed to offset viral insults. As one example, nonsense-mediated mRNA decay, a cellular quality-control mechanism ensuring the translational fidelity of mRNA transcripts, has been used to restrict virus replication in both plants and animals. In response, viruses have develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…We selected TurboID, an engineered promiscuous biotin ligase that is optimized for biotinylation of exposed lysine residues on proteins within a ~10 nm radius (Branon et al, 2018). Since the EBOV polymerase (EBOV_pol) requires both L and VP35 proteins to function, we used the split-TurboID system, which was engineered from full-length TurboID to produce two inactive fragments (Cho et al, 2020), sN-and sC-TurboID, that when brought together via protein-protein interactions, reconstitute full-length TurboID and its biotin ligase activity. To construct EBOV L-sNTurboID, we inserted sNTurboID into a predicted flexible loop region in EBOV L, a site that can tolerate insertion of mCherry (Hoenen et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We selected TurboID, an engineered promiscuous biotin ligase that is optimized for biotinylation of exposed lysine residues on proteins within a ~10 nm radius (Branon et al, 2018). Since the EBOV polymerase (EBOV_pol) requires both L and VP35 proteins to function, we used the split-TurboID system, which was engineered from full-length TurboID to produce two inactive fragments (Cho et al, 2020), sN-and sC-TurboID, that when brought together via protein-protein interactions, reconstitute full-length TurboID and its biotin ligase activity. To construct EBOV L-sNTurboID, we inserted sNTurboID into a predicted flexible loop region in EBOV L, a site that can tolerate insertion of mCherry (Hoenen et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Here we discovered two critical players in the cellular nonsense-mediated decay (NMD) pathway, UPF1 and GSPT1, which can both regulate EBOV infection. Although the role of NMD decay in virus infection has been examined for positive-strand and double-strand RNA viruses, retroviruses and influenza (Balistreri et al, 2017;Declercq et al, 2020;Popp et al, 2020;Tran et al, 2021), how NMD affects negative-strand RNA viruses like EBOV that replicate in the cytoplasm remains unclear. In the cellular NMD pathway, UPF1 degrades aberrant mRNAs by binding to the translation-termination complex (GSPT1/eRF3-eRF1) upon ribosomal recognition of a premature termination codon (PTC) in the mRNA (Kurosaki and Maquat, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[41] Thus, viral proteins that inhibit NMD mechanisms are likely to benefit viral replication. This hypothesis has received experimental evidence from studies done, for example, on human and animal coronaviruses, hepatitis C virus, West Nile, Dengue, Semliki Forest, Zika or human Tlymphotrophic type 1, viruses (reviewed in [1][2][3]).…”
Section: Viruses Fight Nmdmentioning
confidence: 99%
“…It has been widely reported that viral RNA is a target of NMD, and RNA viruses have evolved their own strategies to protect viral RNA from NMD [28][29][30][31]. HTLV-1 encodes more than 10 different viral proteins within its 9 kbp proviral genome.…”
Section: Introductionmentioning
confidence: 99%